Prinsip Keadilan Restoratif Dalam Penghentian Penuntutan Perkara Pidana Berdasarkan Peraturan Jaksa Agung Nomor 15 Tahun 2020 - Ainul Azizah; I Gede Widhianan Suarda; Mardiyono Mardiyono (Pusat Riset dan Inovasi Nasional, 2023)
Restorative justice or better known as restorative justice in the development of schools of law and punishment in human civilization, where the state returns the ius ponale and ius poniendi mandates to the community within the framework of healing, recovery and recovery. Restorative justice is a concept of thinking that responds to the development of the criminal justice system by focusing on the need to involve actors, communities and victims as a social recovery step in social relations. The principle of restorative justice is one of the principles of law enforcement in resolving cases which can be used as an instrument of recovery and has been implemented by the supreme court in the form of policy implementation (Supreme Court Regulations and Supreme Court Circulars). Restorative justice is considered a model of modern punishment that is more humane than the retributive justice used in the current justice system. One of the applications of this is the termination of the prosecution process by the prosecutor.